The Impact of Regional Autonomy on Community Welfare Enhancement - Moh. Ali; ST. Sariroh; Rumawi Rumawi; Abdelmajid Idris Mohammed Khalil (Constitution Journal, 2026)
The implementation of regional autonomy in Indonesia since the Reform Era, particularly through Law Number 23 of 2014 on Regional Government, has been expected to enhance public welfare through the decentralization of authority and the strengthening of regional capacity. However, in practice, several challenges persist, including regional development disparities, the low quality of public services, and the suboptimal management of local resources. Data from the Central Bureau of Statistics indicate that poverty rates in several underdeveloped regions remain above the national average, while the Human Development Index (HDI) in certain areas is still categorized as moderate to low. This study aims to analyse the implications of the implementation of regional autonomy on improving community welfare. This normative research employs a descriptive-analytical method and a statutory approach, drawing on literature studies and secondary data analysis from government reports and international journals. The findings reveal that regional autonomy has positive implications in improving access to public services, accelerating infrastructure development, and encouraging community participation in local development. Nevertheless, its effectiveness is still influenced by the institutional capacity of local governments, the quality of human resources, as well as the level of transparency and accountability in governance. Therefore, strengthening good governance practices and enhancing the capacity of the regional apparatus are essential to ensure that the primary objective of regional autonomy in improving public welfare can be achieved optimally.